Application of School Activity Plans and Budgets (SAPB) in School Activity Planning and Budget: A Case Study at State Kindergartens in the South Jakarta Administrative Area DKI Jakarta - Ramadhan, Laila Sari; Ahmad, Masduki; Rochimah, Heni (Journal of English Language and Education, 2025)
The School Activity and Budget Plan Application (SAPB) plays an important role in the digitalization of school financial management, promoting transparency and accountability. However, the implementation of SAPB often faces technical and non-technical challenges that hinder the effective management of school funds. This study aims to analyze the implementation of SAPB in supporting financial governance in schools located in South Jakarta. The research used a mixed-methods approach, collecting data through questionnaires and interviews with principals, school treasurers, and operators. The findings indicate that SAPB significantly helps in financial supervision, transaction recording, and data synchronization, yet technical issues such as system errors and slow access persist, along with non-technical challenges such as inadequate training and support. This study concludes that improving SAPB’s technical quality, enhancing user capacity through comprehensive training, and strengthening      infrastructure      support      are      essential      to      optimize      SAPB      implementati on.